Afterword: Reflections on the Motley Crew as Port City Proletariat. (26th March 2019) - Rediker, Marcus
Abstract: This essay reflects on the workers in Atlantic and Indian Ocean port cities who made possible the rapidly expanding system of global capitalism between 1650 and 1850. In all of the ports treated in this volume, a mixture of multi-ethnic, male and female, unskilled, often unwaged laborers collectively served as the linchpins that connected local hinterlands (and seas) to bustling waterfronts, tall ships, and finally the world market. Although the precise combination of workers varied from one port to the next, all had an occupational structure in which half or more of the population worked in trade or the defense of trade, for example in shipbuilding/repair, the hauling of commodities to and from ships, and the building of colonial infrastructure, the docks and roads instrumental to commerce. This "motley crew" – a working combination of enslaved Africans, European/Indian/Chinese indentured servants, sailors, soldiers, convicts, domestic workers, and artisans – were essential to the production and worldwide circulation of commodities and profits.